Physical activity and its importance for the health of elderly - Sztandera, Paulina (Journal of Education, Health and Sport, 2017)
Introduction and aim of the study. World society is aging. In Poland, in 2015 the proportion of older people is almost 23%, and the world is 12%. Forecasts show that by 2050 this proportion will reach 32.7%, the world 22%, and 1 in 5 people will be 60+. The purpose of the study was to analyze the literature of physical activity and its benefits to elderly people’ health. Actual knowledge. The health condition worsens with age, the number of long-term health problems and chronic diseases rising with age. These problems are mainly related to cardiological problems, joint problem and diabetes. The World Health Organization has pointed out that physical activity has measurable effects on the health of the elderly. Summary.From the available literature, there is clearly a positive effect of physical activity on the health of people in the third period of life. Physical activity started in any age will have beneficial health effects associated with improved functional status, improved quality of life and mood.